Inhibitory effects of antisense RNA of HAb18G/CD147 on invasion of hepatocellular carcinoma cells in vitro - Li, Yu (World J Gastroenterol, 2003)
AIM: To study the inhibitory effects of antisense RNA of HAb18G/CD147 on invasion of hepatocellular carcinoma (HCC) cells in vitro. METHODS: Antisense RNA of HAb18G/CD147 vector PCI-asHAb18G was constructed by reversely inserting HAb18G/CD147 cDNA to eukaryotic expression vector PCI-neo. The HCC cell line HHCC was transfected by PCI-asHAb18G via cation liposome. Expression of HAb18G/CD147 of transfected cells selected by G418 (geneticin) was observed by immuno-histochemical SP staining and FACS (fluorescence activated cell sorting). Gelatin zymography was used to determine the effect of PCI-asHAb18G on reducing secretions of MMP-2 and MMP-9 of the transfected cells. Boyden chamber was employed to test the invasion of HCC cells in vitro. RESULTS: The construction of antisense RNA vector PCI-asHAb18G was verified correct by partial nucleotide sequencing and restricted endonuclease digestion. The expression of HAb18G/CD147 in transfected HHCC was inhibited by PCI-asHAb18G. Secretions of MMP-2 and MMP-9 of transfected HHCC were reduced and the invasion of transfected HHCC was inhibited compared to HHCC, respectively. CONCLUSION: Invasion of HCC cells can be inhibited by antisense RNA of HAb18G/CD147. HAb18G/CD147 may be used as a potential target of drugs for anti-invasion and metastasis of HCC.